2023
DOI: 10.1007/s10802-022-01020-1
|View full text |Cite
|
Sign up to set email alerts
|

Intolerance of Uncertainty and Emotional Processing in Adolescence: Separating Between-Person Stability and Within-Person Change

Abstract: Previous research on the relation between Intolerance of Uncertainty (IU) and Emotional Processing (EP) during adolescence is limited. The present study aimed to clarify how IU and EP evolve over time, to what extent they are related, and whether changes in one precede or follow changes in the other. A total of 457 Italian adolescents (53.1% girls) aged 11 to 18 years (M = 14.1 ± 2.27) completed the IU and EP scales on three separate occasions three months apart (T1, T2, and T3). Data were modeled using a Rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 80 publications
1
1
0
Order By: Relevance
“…First, we demonstrated a longitudinal stability of the trait constructs measured by the PSWQ and the IUS-R scales, in line with studies that showed how IU and trait of worry seems to be stable over time and across situation (e.g., Dugas et al, 2004 ; Mahoney and McEvoy, 2012 ; Brintzinger et al, 2021 ; Lauriola et al, 2023 ). Coherently with literature (e.g., Carleton et al, 2012 ), we evidenced that the trait of worry and intolerance of uncertainty were related to high levels of worry contents, anxiety, and depressive symptoms, underlying the connection between IU and trait of worry with other psychopathological symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…First, we demonstrated a longitudinal stability of the trait constructs measured by the PSWQ and the IUS-R scales, in line with studies that showed how IU and trait of worry seems to be stable over time and across situation (e.g., Dugas et al, 2004 ; Mahoney and McEvoy, 2012 ; Brintzinger et al, 2021 ; Lauriola et al, 2023 ). Coherently with literature (e.g., Carleton et al, 2012 ), we evidenced that the trait of worry and intolerance of uncertainty were related to high levels of worry contents, anxiety, and depressive symptoms, underlying the connection between IU and trait of worry with other psychopathological symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…This approach assumes that a tolerant person is able to effectively resolve conflicting and ambiguous situations, regulate information processing, adequately and critically evaluate situations of uncertainty, be receptive to uncertainty, take responsibility for their decisions and choices, and turn the acquired knowledge and information into experience problem-solving. Investigating the issue of tolerance to uncertainty and its connection with human maturity, M. Lauriola et al (2023) defines these aspects as mutually complementary processes, where a person's ability to perceive and understand himself and his emotions, to creatively approach the solution of everyday tasks, as well as to be responsible and open to new experiences contributes to the development of personality tolerance. Studying the issue of tolerance as a personal attribute of a person, the author also notes that the maturity of a person is characterized by his readiness to take responsibility for his actions, behaviour and decisions, which allow the individual to form self-identity and self-respect in his mind.…”
Section: Discussionmentioning
confidence: 99%